Choosing NVivo to support phenomenographic research in networked learning - Asensio, Mireia (Proceedings of the International Conference on Networked Learning, 2000)
This poster will describe the rationale for choosing QSR NUD*IST Vivo (NVivo) as a software package to support the management and analysis of data generated from the JISC/CALT-funded ’Networked Learning in Higher Education’ project at CSALT, Lancaster University. This project aims primarily at understanding the student’s experiences of participating in a networked learning course. The basis of this research is phenomenographic and draws on individual interviews and observations. It is complemented by a survey based study of students’ approaches to learning in networked learning environments. The rationale for choosing NVivo was thus aligned to the aims of the project, the characteristics of phenomenography and the type of data that the research is generating. Our experience of NVivo is still at a formative stage and with this poster we hope to initiate a dialogue among researchers, on the implications and experiences of using this type of software to support research in networked learning.